Supplier performance evaluation factors for agroindustrial supply chain: A systematic review - Wike Agustin Prima Dania; Aldo Tafarel; Riska Septifani; Yousef Amer; Linh Doan (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Supplier performance is critical in maintaining the stability of the supply chain activities in the agroindustry. Their performance needs to be assessed using relevant factors to choose reliable and dependable suppliers. A significant amount of research has been done to examine essential factors in selecting reliable suppliers in supply chains from various perspectives. The divergence of research findings has led to many assessment factors that must be considered when choosing the supplier. Therefore, this study aimed to analyze factors affecting agroindustry supplier performance using a systematic review. The research from reliable databases such as Elsevier, Emerald, Proquest, and Taylor & Francis from 2010 to 2020 has been analyzed. Similarity and relevance analysis has been applied to form the factors and eliminate the redundant and irrelevant factors. As a result, fourteen suppliers’ performance factors to support an effective supply chain system are identified. These factors include customer care, economics, quality improvement, stakeholder coordination, production performance, organizational improvement, human resources, food safety, risk factors, company image, market, geography, corporate social responsibility (CSR), and environmental management system (EMS).